Burial Mound People - Potrebica, Hrvoje (2007)
This session follows four previous sessions organized with subject of funerary practices with special concern to archaeology of burial mounds. So far, we were mostly discussing different approaches to burial mounds as special category of monuments, including their spatial and social aspects, as well as monumentality. This time we will turn to their “human content”, or “actual inhabitants” of burial mounds, and go back to the fundamental question: “Who were people buried in burial mounds?” The session will therefore discuss problems related to different expressions of identity of buried individuals related to the community they are part of and which is in a way represented by their burial monuments. Some of aspects which will be addressed in papers within this session are: 1. personal identity - naming the dead: individuality vs. symbolic representation - what features identify the dead as an individual (if any): - within the grave - mound construction 2. group identity - relation to the groups within the community - clustering of individual burial mounds or multiple burials - whom do they belong to? - clan/family vs. individual - gender - class 3. identification of status - can we identify social status that buried individual had within the community or any group within that community and how? - in what extent burials reflect status of the deceased vs. status of the individual/group/community which is performing burial and building the mound itself? 4. communal identity - “us and them”
Projekt MZOS
ENG